Perception of nursing as a scientific discipline and nurse profession by students of nursing - Anna Lewandowska; Lucyna Lichota; Tomasz Lewandowski; Barbara Laskowska (Kazimierz Wielki University, 2018)
Introduction: The nurse according to the Supreme Chamber of Nurses and Midwives is a person able to recognize the health condition of an individual or group and can create a care plan and realize it. The nurse should be primarily autonomous in making decisions about nursing care and organizing nursing care. Each competent nurse can make a proper assessment of a given situation, makes decisions efficiently and is able to quickly select the right methods of conduct. The awareness that science is always the foundation of practice is extremely important. This is how the profession of a nurse was shaped over the years. These scientific achievements greatly influence the increase of the professional nurse's prestige. Objective: The aim of the work is to gain knowledge about the perception of nursing, as a scientific discipline and nurses, by students of the nursing field. Material and methods: The study covered 100 people who are students of nursing, finishing the three-year education period. The selection of respondents was random. The study group consisted of 100% women aged 20-35, living in urban areas (51%) and rural (49%). The research method used in the work is a diagnostic survey. The research tool used is a self-help questionnaire. Results: Nursing understood 16% of respondents as a profession, 3% considered them as a scientific discipline, 1% as a learning system. The vast majority of respondents (92%) stated that nursing is both theoretical and practical science. The nurses' forms of activity, which contribute to the development of nursing, 73% of them reported upgrading professional qualifications, 7% writing scientific papers, 2% participation in scientific research, 1% participation in the preparation of apprentices to the profession and 1% activity in organizations unions. The most important features that should be possessed by a good nurse include: diligence and accuracy of performed procedures (25%), possessing rich knowledge in the field of medical sciences (55%), care (40%), cordiality and kindness (39%), patience and forbearance (38%), communicativeness (38%) and a humane attitude towards the patient (19%). Conclusions: Nursing students perceive nursing as a scientific discipline, occupation, education system and subsystem in the care system. According to the respondents, nursing has a chance to become a separate field of science in the future, if it continues its scientific development. According to the respondents, the nurse should be: friendly, responsible for the work to be done, and have extensive knowledge in the field of medical sciences.